Intralymphatic glutamic acid decarboxylase administration in type 1 diabetes patients induced a distinctive early immune response in patients with DR3DQ2 haplotype - Puente-Marin, Sara; Dietrich, Fabrícia; Achenbach, Peter; Barcenilla, Hugo; Ludvigsson, Johnny; Casas, Rosaura (Frontiers in Immunology, 2023)
GAD-alum given into lymph nodes to Type 1 diabetes (T1D) patients participating in a multicenter, randomized, placebo-controlled double-blind study seemed to have a positive effect for patients with DR3DQ2 haplotype, who showed better preservation of C-peptide than the placebo group. Here we compared the immunomodulatory effect of GAD-alum administered into lymph nodes of patients with T1D versus placebo with focus on patients with DR3DQ2 haplotype. Methods GAD autoantibodies, GADA subclasses, GAD65-induced cytokine secretion (Luminex panel) and proliferation of peripheral mononuclear cells were analyzed in T1D patients (n=109) who received either three intra-lymphatic injections (one month apart) with 4 µg GAD-alum and oral vitamin D supplementation (2000 IE daily for 120 days), or placebo. Results Higher GADA, GADA subclasses, GAD65-induced proliferation and cytokine secretion was observed in actively treated patients after the second injection of GAD-alum compared to the placebo group. Following the second injection of GAD-alum, actively treated subjects with DR3DQ2 haplotype had higher GAD65-induced secretion of several cytokine (IL4, IL5, IL7, IL10, IL13, IFNγ, GM-CSF and MIP1β) and proliferation compared to treated individuals without DR3DQ2. Stratification of samples from GAD-alum treated patients according to C-peptide preservation at 15 months revealed that “good responder” individuals with better preservation of C-peptide secretion, independently of the HLA haplotype, had increased GAD65-induced proliferation and IL13 secretion at 3 months, and a 2,5-fold increase of IL5 and IL10 as compared to “poor responders”. The second dose of GAD-alum also induced a more pronounced cytokine secretion in “good responders” with DR3DQ2, compared to few “good responders” without DR3DQ2 haplotype. Conclusion Patients with DR3DQ2 haplotype had a distinct early cellular immune response to GAD-alum injections into the lymph node, and predominant GAD65-induced IL13 secretion and proliferation that seems to be associated with a better clinical outcome. If confirmed in the ongoing larger randomized double-blind placebo-controlled clinical trial (DIAGNODE-3), including only patients carrying DR3DQ2 haplotype, these results might be used as early surrogate markers for clinical efficacy.